(untitled) (Research, Society and Development, 2021)
In this article we briefly present dialectics as a possibility of explanation and interpretation of reality. The historical-dialectical materialism was the methodological/theoretical path we followed, aiming to apprehend the different concepts about university extension experienced in a contradictory and unequal society. This is a bibliographical study. The results achieved reveal that the extension in Brazil, throughout its history, presents distinct moments: the first moment corresponds to technical knowledge, through courses directed to the popular classes, which were influenced by European popular universities. In the second moment, inspired by the North American model, we have an extension aimed at providing services to farmers, in the form of technical assistance, in the area of agriculture and livestock. This model of extensionist practices followed the interests of the capital, centered under the discourse of the hegemonic groups, preaching that these actions had the purpose of developing the country. And in the third moment, we have the Forproex being a national reference that has aimed to discuss the concept, guidelines, principles and objectives of the extension.